Pemberdayaan Masyarakat Melalui Program Agrowisata Di Desa Bojongnangka Kabupaten Pemalang - Mahardika, Genta Bernard; Asshofi, Izza Ulumuddin Ahmad; Wijaya, Muhammad Askha Rafliansyach; Ariestya, Natasya Sekar; Shan, Ariel Sabella Siva; Safitri, Rachma Hani Rahayuning; Lestari, Fresta Indah; Albertus, Angelina; Marisa, Kintan; Hergiandari, Ganjar; Handoyo, Siaw Armando (PT. Riset Press International, 2023)
The agro-tourism pilot project in the village of Bojongnangka began at the end of 2021 with the construction of a tourist attraction, Gatra Kencana, an educational tourism destination for rice fields. Even though the tourist destination is built on top of the rice fields, the rice fields can still be planted with rice with homemade organic fertilizers. However, to become an agro-tourism village has not be followed with the development of tourism human resources and agro-tourism packages so that the beneficiaries have not be extended to the Bojongnangka village community. The absence of tourism activists who manage tour operations and the absence of tour packages to collaborate with community participation are challenges in developing this village. The methods used in this community service include the making of agro-tourism community groups, focused group discussions on agro-tourism, and theoretical and practical training carried out by the Village Community Empowerment Program (P2MD) team of Hospitality Management Study Program Dian Nuswantoro University. Finally, through deliberations with village officials and representatives of residents, an agreement was reached in the form of making an agro-tourism community group which was ratified through a Decree from the Head of Bojongnangka Village, 5 agro-tourism packages, and integration of tourism businesses to make Gatra Kencana a tourism icon in Bojongnangka Village. Moreover, the team also develop empowerment program of MSMEs in agro-tourism packages, signing a memorandum of understanding with the Association of Indonesian Tour Guides of Central Java Chapter and creating a display gallery to exhibit agro-tourism products of Bojongnangka village community.